Analysis of complex fluid flow and temperature field in the turbogenerator end region with magnetic shield structure under underexcitation operation. (5th January 2019) - Jichao, Han; Yutian, Sun; Ping, Zheng; Dajun, Tao; Yanling, Lv; Baojun, Ge; Weili, Li
Abstract: The large electromagnetic losses and high temperature rise under underexcitation operation are the main issues of large turbogenerator design. In order to study the eddy current losses, fluid velocity, and temperature distribution in the turbogenerator end region with magnetic shield structure under underexcitation operation, three-dimensional transient electromagnetic field of a 1250 MW turbogenerator end region is investigated. The losses of end parts and stator end cores (heat source) are obtained under underexcitation operation. Velocity values of different inlets and pressure value of fan outlet (boundary condition) are determined by flow network calculation. Meanwhile, three-dimensional fluid and thermal fields are calculated. The distribution of fluid flow between magnetic shields is obtained. The temperature distribution of end parts and stator end cores in the end region of large turbogenerator is studied under underexcitation operation with 0.9 pf lead. Calculation results are compared with experiment data, which provides a reliable basis for the design and operation of larger turbogenerator.